Women’s Role in ICT Accounting Research: An Account from Self- Reflection - Wong, E.S.K. (Macrothink Institute, 2010)
The term feminism, which began to gain ground in the 1970s, is used by those who object to the perceived deprivation of a woman’s right to proper professional development. Very little evidence exists, however, as to why so few women have undertaken careers as an Academic researcher. John Lucas (1973) suggests that the feminist debate may lead to the application of certain concepts of justice, equality, and humanity. This being so, a central question for this paper is “Why is the academic management industry far from being gender neutral?” The author argues that such issues need to be highlighted, as he perceives that society as it stands is still unfair to women, and that this unfairness should be addressed. The paper also identifies that there are still, unanswered questions as to whether discrimination against suitably qualified women for such positions could ever be defended according to the current principles of social justice.